SIMULATION STUDY ON TEMPERATURE FIELD OF FRICTION PAIR IN SYNCHRONIZER SYNCHRONIZATION PROCESS - ZHANG ZhiGang; PENG CaiHong; ZHANG ZiYang; SU MengYue (Jixie qiangdu)
Combined with the actual structure and working conditions of the synchronizer, AMESim, MATLAB and ABAQUS software are used to establish the gear shifting dynamics model, friction contact mechanism model and finite element analysis model of the synchronizer. The thermal structure coupling method is used to simulate the temperature characteristics of synchronizer during synchronization. Based on the mechanical result of the synchronizer and the friction contact mechanism and thermal analysis theory of the synchronizer, the thermal characteristics of the frictional contact area during the synchronization phase of the synchronizer are modeled, simulated and analyzed. The results show that the maximum temperature of the model is in the middle of the whole friction area, the maximum temperature of the friction surface of the synchronous lock ring is 106.0℃, and the maximum temperature of the friction cone surface of the meshing ring is 78.3℃.The analysis of the temperature field of the synchronizer lays a foundation for the subsequent analysis of the thermal failure form and mechanism of the friction contact surface.